Constructive design of bonded FRP mixed joints under consideration of edge effects - Göddecke, Johannes; Meschut, Gerson; Teutenberg, Dominik (12TH EUROPEAN ADHESION CONFERENCE (EURADH 2018))

FOREL-Studie 2018: Ressourceneffizienter Leichtbau für die Mobilität (Wandel-Prognose-Transfer) - Göddecke, Johannes; Meschut, Gerson

Numerical Investigation of the Tool Load in Joining by Forming of Dissimilar Materials Using Shear-Clinching Technology - Wiesenmayer, Sebastian; Müller, Martin; Dornberger, Peter; Han, Daxin; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Modern developments in the automotive sector are motivated by the objective of lowering the emission of pollutants. In contrast, growing demands for safety and comfort lead to a potential increase of the weight of vehicles. Thus, the consequent use of lightweight design is indispensable. This includes the use of different materials for the construction of car bodies. Because of various material properties, joining of dissimilar materials is challenging and requires often the application of non-thermic processes like riveting or clinching. These processes are limited by the mechanical properties of the joining partners. Especially the increasing use of ultra-high strength alloys, like the hot stamped steel 22MnB5, makes the development of new joining technologies necessary. One of these innovative technologies is shear-clinching. By combining shear-cutting and clinching in one process, this technology produces durable and tight connections of dissimilar materials with high differences regarding strength and formability. In contrast to shear-cutting the die-sided material has no contact with the punch. Since the process of shear-clinching is a combination of cutting and joining using the same tool, the tool loads differ from common shear-cutting. Especially cutting hot stamped steels is a challenge due to their high ultimate strength which leads to high tool loads. Thus, the analysis of the load condition is essential for the dimensioning of durable and wear resistant tools. Hence, the scope of this paper is a numerical investigation of the tool loads during the indirect cutting process and the subsequent step of joining by forming during shear-clinching. Since an experimental investigation of the occurring tool loads in the closed process is not practicable, the finite element method has to be used. Therefore, a damage-based numerical model is set up to enable the coupled simulation of the combined cutting and joining process and the resulting tool loads. This allows the analysis of the loads during the whole process, identifying the influences of materials and sheet thicknesses.

Investigation of the influence of tool-sided parameters on deformation and occurring tool loads in shear-clinching processes - Han, Daxin; Hörhold, Réjane; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Procedia Manufacturing)

Innovative joining technology for multi-material applications with high manganese steels in lightweight car body structures - Ivanjko, Martin; Meschut, Gerson (Welding in the World)

Habitual Fructose Intake Relates to Insulin Sensitivity and Fatty Liver Index in Recent-Onset Type 2 Diabetes Patients and Individuals without Diabetes. - Weber, KS; Simon, MC; Strassburger, K; Markgraf, DF; Buyken, Anette; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Nutrients)

„Persons in the Shadow“ und ihre Bedeutung für die Entwicklung von Lehrerexpertise - Bloh, Thiemo; Bloh, Bea

Professionelle Lerngemeinschaften und Communities of Practice – Unterschiedliche theoretische Ansätze zur Erforschung von Lehrerkooperation - Bloh, Thiemo; Bloh, Bea; van Ophuysen, Stefanie

Vermittlungsstrategien zum Forschenden Lernen in der Lehrerbildung - Was nutzt der Nutzen? - Bloh, Bea; Schürer, Sina; Behrmann, Lars; van Ophuysen, Stefanie

Fertility and Modernization: The Role of Urbanization in Developing Countries - Gries, Thomas; Grundmann, Rainer (Journal of International Development)

Als Wirtschaftsinformatiker die digitale Transformation in Organisationen gestalten - Kundisch, Dennis; Beverungen, Daniel

Disaggregating User Evaluations Using the Shapley Value - Feldotto, Matthias; Haake, Claus-Jochen; Skopalik, Alexander; Stroh-Maraun, Nadja (Proceedings of the 13th Workshop on Economics of Networks, Systems and Computation (NetEcon 2018))
We consider a market where final products or services are compositions of a number of basic services. Users are asked to evaluate the quality of the composed product after purchase. The quality of the basic service influences the performance of the composed services but cannot be observed directly. The question we pose is whether it is possible to use user evaluations on composed services to assess the quality of basic services. We discuss how to combine aggregation of evaluations across users and disaggregation of information on composed services to derive valuations for the single components. As a solution we propose to use the (weighted) average as aggregation device in connection with the Shapley value as disaggregation method, since this combination fulfills natural requirements in our context. In addition, we address some occurring computational issues: We give an approximate solution concept using only a limited number of evaluations which guarantees nearly optimal results with reduced running time. Lastly, we show that a slightly modified Shapley value and the weighted average are still applicable if the evaluation profiles are incomplete.

What Drives Paid Search Success: A Systematic Literature Review - Schlangenotto, Darius; Kundisch, Dennis; Poniatowski, Martin (Proceedings of the 24th Americas Conference on Information Systems (AMCIS))

Body dissatisfaction in normal weight children – Sports activities and motives for engaging in sports - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J.; Trojan, J. (European Journal of Sport Science)

Vorausschau und Technologieplanung. 14. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 8. und 9. November 2018 - Gausemeier, Jürgen

Wie kann der Aufbau einer forschenden Grundhaltung im Praxissemester gelingen? Erste Ergebnisse einer qualitativen vergleichenden Fallstudie - Homt, Martina; van Ophuysen, Stefanie (Praxisphasen in der Lehrerbildung im Fokus der Bildungsforschung)

Die Studienprojekte im Praxissemester. Wie nehmen Studierende die universitäre Vorbereitung in den Projektseminaren wahr? - Homt, Martina; van Ophuysen, Stefanie (Herausforderung Lehrer_innenbildung. Zeitschrift zur Konzeption, Gestaltung und Diskussion)
An der Westfälischen Wilhelms-Universität Münster gilt Forschendes Lernen als wesentliche Zielsetzung des Praxissemesters. Die Lehramtsstudierenden sollen dazu befähigt werden, mit einer explizit forschenden Grundhaltung zu lernen. Dies erfolgt im Praxissemester insbesondere in Form von drei Studienprojekten, die die Studierenden in drei Projektseminaren planen, unter Begleitung der Dozierenden in der Praxisphase umsetzen und abschließend reflektieren. Im Fokus des Beitrags stehen die Projektseminare aus Sicht der Studierenden. Wie werden diese in den Projektseminaren an die Studienprojekte herangeführt? Welche Erfahrungen machen sie in den verschiedenen Seminaren und wie bewerten sie diese im Hinblick auf die Vorbereitung der Studienprojekte? Zehn Studierende wurden mittels leitfadengestützter Interviews befragt. Die Daten werden inhaltsanalytisch ausgewertet, um die von den Studierenden wahrgenommene Thematisierung und Vorbereitung auf die Studienprojekte in den Projektseminaren abzubilden. Die Befunde weisen auf differente Ausgestaltungen der Projektseminare sowie auf uneinheitliche Anforderungen und Vorstellungen der Dozierenden hinsichtlich der Studienprojekte hin, welche wiederum auf Seiten der Studierenden zu Unklarheiten führen. Es stellt sich die Frage, inwieweit unter diesen Gegebenheiten der Aufbau einer forschenden Grundhaltung gelingen kann. Die Ergebnisse werden im Hinblick auf Implikationen für die weitere Ausgestaltung der universitären Ausbildung im Kontext des Praxissemesters in Anlehnung an Erkenntnisse aus der Implementationsforschung diskutiert.

Gelingensbedingungen für den Aufbau einer forschenden Grundhaltung im Praxissemester – Die Thematisierung Forschenden Lernens in den Begleitveranstaltungen - Homt, Martina; van Ophuysen, Stefanie

Towards Flexible Demands in Online Leasing Problems. - Li, Shouwei; Markarian, Christine; Meyer auf der Heide, Friedhelm (Algorithmica)

Approximation and Heuristic Algorithms for Computing Backbones in Asymmetric Ad-hoc Networks - Abu-Khzam, Faisal N.; Markarian, Christine; Meyer auf der Heide, Friedhelm; Schubert, Michael (Theory of Computing Systems)